Neglect, Abuse, and Adaptive Functioning: Food Security and Housing Stability as Protective Factors for Adolescents - Julia M. Kobulsky; Dalhee Yoon; Miguel T. Villodas; Brittany R. Schuler; Rachel Wildfeuer; José N. Reyes (MDPI AG, 2022)
This study addresses gaps in knowledge of protective factors that support adaptive functioning among maltreated adolescents. The sample included 1003 high-risk youths participating in the Longitudinal Studies of Child Abuse and Neglect (53% female, 56% Black, and 82% living in poverty). Adolescent neglect (Exposure to Risky Situations, Lack of Monitoring, Inattention to Basic Needs, Permitting Misbehavior, Lack of Support) and physical, sexual, and emotional abuse were self-reported at age 16. Age 18 adaptive functioning measures included healthcare receipt (medical, dental, and mental health), self-rated global health, high school graduation or enrollment, prosocial activities, peer relationships (Companionship, Conflict, Satisfaction, and Intimacy), and independent living skills. Previous childhood maltreatment, demographics, and earlier prosocial activities and peer relationships were controls. Structural equation modeling showed that adolescent neglect and abuse were associated with lower adaptive functioning. Multigroup models showed protective effects for food security on the relationships between sexual abuse and self-rated health and between Inadequate Monitoring and Companionship. Housing stability buffered relationships between Inadequate Support and high school graduation or enrollment and between Permitting Misbehavior and independent living skills. Findings imply the need for adolescent-focused prevention, including the promotion of food security and housing stability to support adaptive functioning in maltreated adolescents. However, notable mixed findings show the need for additional research.